Impact of Phosphate Availability on Membrane Lipid Content of the Model Strains, Streptomyces lividans and Streptomyces coelicolor - Lejeune, Clara; Abreu, Sonia; Chaminade, Pierre; Dulermo, Thierry; David, Michelle; Werten, Sebastiaan; Virolle, Marie-Joelle (Frontiers in Microbiology, 2021)
In this issue we demonstrated that the phospholipid content of S. lividans varies greatly with Pi availability being was much lower in Pi limitation than in Pi proficiency whereas that of Streptomyces.coelicolor varied little with Pi availability. In contrast the content in phosphate free ornithine lipids was enhanced in both strains in condition of phosphate limitation. Ornithine lipids biosynthesis starts with the N-acylation of ornithine to form lyso-ornithine that is then O-acylated to yield ornithine lipid. The operon sco1222-23 was proposed to be involved in the conversion of specific amino acids into ornithine in condition of phosphate limitation whereas the sco0921-20 operon encoding N- and O-acyltransferase, respectively, was shown to be involved in the biosynthesis of these lipids. The expression of these two operons was shown to be under the positive control of the two components system PhoR/PhoP and thus induced in phosphate limitation. The expression of phoR/phoP being weak in S. coelicolor, the poor expression of these operons resulted into a five fold lower ornithine lipids content in this strain compared to S. lividans. In the deletion mutant of the sco0921-20 operon of S. lividans, lyso-ornithine and ornithine lipids were barely detectable and TAG content was enhanced. The complementation of this mutant by the sco0921-20 operon or by sco0920 alone restored ornithine lipids and TAG content to wild type level and was correlated with a 2 fold increase in the cardiolipin content. This suggested that SCO0920 bears, besides its broad O-acyltransferase activity, an N-acyltransferase activity and this was confirmed by the detection of lyso-ornithine in this strain. In contrast, the complementation of the mutant by sco0921 alone had no impact on ornithine lipids, TAG nor cardiolipin content but was correlated with a high lyso-ornithine content. This confirmed that SCO0921 is a strict N-acyltransferase. However, interestingly, the over-expression of the sco0921-20 operon or of sco0921 alone in S. coelicolor, led to an almost total disappearance of phosphatidylinositol that was correlated with an enhanced DAG and TAG content. This suggested that SCO0921 also acts as a phospholipase C, degrading phosphatidylinositol to indirectly supply of phosphate in condition of phosphate limitation.